Analysis of hazardous chemicals by "stand alone" drift tube ion mobility spectrometry: a review. Issue 9 (12th February 2020) - Armenta, S.; Esteve-Turrillas, F. A.; Alcalà, M.
Abstract : Drift tube-ion mobility spectrometry (DT-IMS) is a widely used technique for the determination of semi-volatile hazardous chemicals based on gas phase ion separation under an electric field by differences in ion mobilities. Abstract : Ion mobility spectrometry (IMS) is a widely used technique based on gas phase ion separation under an electric field by differences in ion mobilities. In the last decade, IMS techniques have received increased attention due to their high operational speed and sensitivity. Currently, there are different IMS devices focused on solving different analytical performances, mainly based on linear drift tube (DT IMS), traveling wave, and field asymmetric waveform ion mobility spectrometers. In this review we summarize the main applications of DT-IMS devices for the determination of semi-volatile hazardous chemicals such as: illegal drugs, pesticides, explosives, chemical warfare agents, and others, in different matrices, in order to provide a detailed view of the analytical features of the technique.